Tracing the untraceable: fingerprinting pollutants through environmental forensics - Zakaria, Mohamad Pauzi (Universiti Putra Malaysia Press, 2014)
Investigation of source, distribution and transport pathways of compound-specific petroleum hydrocarbon pollution is not well documented in Malaysia. In the beginning, research on petroleum hydrocarbon pollution was bulk analysis in nature. Bulk analysis of petroleum hydrocarbons gives a broad spectrum of total petroleum hydrocarbon pollution that may also include non-toxic biogenic (natural) sources. Since petroleum hydrocarbon consists of many classes of hydrocarbons and each of them has different characteristics and toxicities, compound-specific analysis of the pollutants is necessary. Therefore, in the late 1990’s, intense research by our group on compound-specific petroleum hydrocarbon opened a new phase in Malaysia using environmental forensics and fingerprinting techniques. Intensive research on the source, distribution and transport pathways of compound-specific petroleum hydrocarbon pollution was conducted in terrestrial, atmospheric and aquatic environments in Malaysia. It was found that sediments from Malaysian rivers and estuaries are contaminated with petrogenic polycyclic aromatic hydrocarbons. Furthermore, Malaysian rivers and estuaries were found to be contaminated with PAHs originated from landfill leachates. Major contributor of land-based petroleum hydrocarbon pollution was that of the used-crank case oil. Malaysian coastal beaches were also contaminated with tar balls pollution originated from previous offshore oil spills by foreign oil tankers and domestic oil spillages. PAHs were also found in coastal marine organisms including fishes in aquaculture cages. Atmospheric transport of pyrogenic PAHs in Malaysia was influenced by mobile sources such as motor vehicles and biomass burning. Monitoring of PAHs using our techniques was applied to Asian countries and results showed that petroleum hydrocarbon pollution is widespread and pose significant human health threat. Our research covers land, atmospheric and sea-based sources of petroleum hydrocarbon pollution. Our research style and techniques are now applied to other contaminants of human concern such as pharmaceutical and personal care products (PCPPs), sewage pollution, PFOA and PFOS, PBDE, and heavy metals, among others. This lecture will take a closer look at the research and our major contribution to knowledge for scientific and general communities at large.